The Positive Impact of Artificial Intelligence (AI) on Students’ Independent Learning - Belina Lalan; Zahfa Zalia Puce; Iren Tinus (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Artificial Intelligence (AI) has become an important technological innovation that supports learning processes in higher education. This article aims to analyze the positive impact of AI on students' self-directed learning, its applications, and strategies for optimizing its use in academic activities. The study employed a library research method using a qualitative descriptive approach through the analysis of relevant scholarly literature. The findings indicate that AI improves access to learning resources, strengthens critical thinking skills, supports academic task completion, enhances digital literacy, and encourages students to become more independent learners. However, the effective use of AI requires academic integrity, information verification skills, and responsible implementation to maximize its contribution to improving the quality of learning in higher education.